A Newly Developed Compressed Air Cannon Test Bench Designed for Multi-Impact Analysis of Composite Structures - Ayoub Soufri; Ameur Chettah; Benoît Piezel; Christophe Bouvet (Applied Mechanics)
Understanding the response and damage evolution of structures subjected to multiple impact events is essential for designing resilient structures capable of withstanding complex loading scenarios, such as impacts from hail, gravel or foreign object debris. This article presents the development and characterization of a novel test bench, the “Compressed air multi-cannon”, designed specifically for studying the multi-impact behavior of composite materials. This test bench offers advantages over traditional impact testing methods by enabling controlled and adjustable impact parameters, including number of impacts, spatial and temporal lag, energy, angle and impactor dimensions. The primary objective of this work is to provide a detailed description of the test bench design, construction, and validation procedures. Key components such as the pressurized air system, projectile launch mechanism, target mounting arrangement, and data acquisition system are discussed. Experimental methodologies for assessing multi-impact response, specimen preparation, instrumentation, and data analysis techniques are outlined. Through a series of single-impact and multi-impact tests, distinctive damage mechanisms and energy absorption characteristics were observed in composite structures, revealing significant differences in how composites respond under single- and multi-impact conditions. It was found that the single-impact configuration remains particularly critical compared to multi-impact configurations with a high number of impacts. However, further testing is required to determine whether this result holds true under varying impact parameters, highlighting the unique value of this machine for exploring new, realistic questions in the literature.